Heparin Low Doses and Standard Doses Effect on Trans-Radial Catheterization - Muhammad Zafarullah, Gulshan Ahmad, Muhammad Ahmad Raza Butt, Muhammad Imran Ashraf, Muhammad Suleman Khan, Umar Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Transradial artery is being utilized by an expanding number of interventional cardiologists to perform percutaneous interventions. Nevertheless, occlusion of radial artery (RAO) is prominent after transradial (TR) catheterization. Use of anticoagulant drugs is one way to prevent RAO. The conventional dose of heparin is (2000IU-3000IU or 50IU/kg) and high-dose is (5000IU or 100IU/kg). The use of high-dose heparin and standard-dose heparin is still debatable. Objective: The present study will analyze the non-randomized controlled trials of standard and high dose of heparin for the prevention of radial artery occlusion after transradial catheterization. Methodology: A prospective double-blinded non-randomized controlled trial was carried out. Demographic data related to socio-economic status such as their age, occupation, gender, and smoking habits were collected. Grouping was done so that patients may either be placed in group 1 which will receive 2500UI or into group 2 which will get 5000UI of unfractionated heparin. RAO was the key endpoint of our study. Major bleeding, hematomas and radial artery spasm were secondary outcome measure. Results: 471 patients were made part of this study. 235 patients were placed in group A which received 2500IU and 236 were placed in group B which received 5000IU. RAO was noted to be significantly higher in the group the received the standard dose of UFH as compared to the group that received high dose UFH (8 % vs. 3.3 %, p = 0.005). Female gender (OR: 2.951, 95% CI: 1.57-5.46, p = 0.002), hypertension (OR: 0.02, 95% CI: p = 0.005 and standard dose UFH (OR: 2.822, 95% CI: 1.343 – 5.911, p = . 0.007) were found to be the independent predictors of RAO. Conclusion: Weight-adjusted higher dosage of UFH in TRA for diagnosis yielded remarkable results in reducing the rates of early RAO against the standard administered dosage